2020
DOI: 10.12688/gatesopenres.13089.2
|View full text |Cite
|
Sign up to set email alerts
|

Differential privacy in the 2020 US census: what will it do? Quantifying the accuracy/privacy tradeoff

Abstract: Background: The 2020 US Census will use a novel approach to disclosure avoidance to protect respondents’ data, called TopDown. This TopDown algorithm was applied to the 2018 end-to-end (E2E) test of the decennial census. The computer code used for this test as well as accompanying exposition has recently been released publicly by the Census Bureau. Methods: We used the available code and data to better understand the error introduced by the E2E disclosure avoidance system when Census Bureau applied it to 1940 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Traditional disclosure techniques applied to the 2010 census counts include record-swapping, item imputation, whole household imputation, rounding, and top-and bottom-coding (52). The 2010 Demonstration Data Products, which implement DP, work by allocating a "privacy-loss budget" or e (53). The 2010 DP counts were produced under a global e = 6, where personal records use e = 4 and housing records use e = 2 (54).…”
Section: Approach Methods Data and Measuresmentioning
confidence: 99%
“…Traditional disclosure techniques applied to the 2010 census counts include record-swapping, item imputation, whole household imputation, rounding, and top-and bottom-coding (52). The 2010 Demonstration Data Products, which implement DP, work by allocating a "privacy-loss budget" or e (53). The 2010 DP counts were produced under a global e = 6, where personal records use e = 4 and housing records use e = 2 (54).…”
Section: Approach Methods Data and Measuresmentioning
confidence: 99%
“…Our results relate to Flaxman et al, 2020 which observed a similar effect resulting from a non-negativity constraint in the US Census' TopDown differential privacy algorithm. [12] The magnitude of the synthetic error skewing negative in a smaller concentration of zip codes increased as a key indicator became less frequent, which is fundamentally a signal problem in low-density data sets and is not specific to synthetic data generation.…”
Section: Discussionmentioning
confidence: 99%
“…Other Consortial Authors*: Christopher G. Chute 1,2,3,4,5,6,7,8,9,10 , Jon D. Morrow 1,12,13,2,7,9 , Melissa A. Haendel 14,6,10,11 1 clinical data model expertise, 2 data curation, 3 data integration, 4 data quality assurance, 5 funding acquisition, 6 governance, 7 critical revision of the manuscript for important intellectual content, 8 N3C Phenotype definition, 9 project evaluation, 10 project management, 11 regulatory oversight / admin, 12 clinical subject matter expertise, 13 data analysis, 14 funding acquisition *Consortial authorship and corresponding contributions were self-reported as part of the N3C authorship committee review process.…”
Section: Contributor Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These benchmark algorithms' differential privacy proofs cover a wide range of complexity, demonstrating DPCheck can analyze both simple and sophisticated differentially private programs. (4) We present a practical workflow that uses DPCheck to re-implement and test the core differential privacy mechanisms in the Disclosure Avoidance System (DAS) [Petti and Flaxman 2019] designed for 2020 US Census; we also show statistical evidence that our re-implemented core mechanism behaves the same as the unmodified DAS (Section 7.2). (5) We implement DPCheck as an embedded language in Haskell and discuss a type-driven optimization adapted from Torlak and Bodik [2014] to speed up symbolic execution, which improves testing time for some our benchmark algorithms (Section 8).…”
Section: Introductionmentioning
confidence: 99%